Happiness, health, and religiosity: significant associations among Lebanese adolescents - Abdel-Khalek, Ahmed M. (Mental health, religion & culture, 2014)
The present study sought to test for an association between, and sex-related differences in, happiness, health, and religiosity. A sample (N = 239) of Lebanese adolescents was recruited (111 boys and 128 girls). They responded to the Oxford Happiness Inventory, the Satisfaction with Life Scale, the Love of Life Scale as well as five self-rating scales to assess happiness, satisfaction, mental health, physical health, and religiosity. Boys obtained a higher mean score on mental health than did their female counterparts. All the Pearson correlations between the study scales were significant and positive but two. Principal components analysis yielded two salient components in boys and labelled "Happiness", and "Religiosity and health". In girls, only one component was retained, and labelled "Happiness, health, and religiosity". It was concluded that those consider themselves as enjoying happiness, experienced good mental and physical health and more religious.